ANALISIS FILSAFAT EKSISTENSIALISME DALAM PENERAPAN SIKAP DISIPLIN DI SEKOLAH DASAR NEGERI 30 REJANG LEBONG - Suci Skar Kinanti; Farahah Kamilatun Nuha; Nor Hapipah; Mirna Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the philosophy of existentialism in the application of disciplinary attitudes. The research method uses qualitative methods with an existentialist approach. The research results show that students have been instilled with disciplinary attitudes such as self-discipline and self-awareness. Self-discipline can be done by students obeying the rules that the teacher and school have made and always being punctual in doing things such as not coming to school late, wearing a neat uniform. Discipline also requires supporting factors and one of them is the role of parents at home because it is useless if at school you apply discipline and at home your parents don't pay attention to discipline. In the concept of self-awareness, students must have a sense of responsibility and independence. Like if you are given a task and complete the task on time independently. And not only that, students are also given the responsibility of class picketing, so students are obliged to carry out this responsibility by cleaning the class in a form of self-awareness.